2013
DOI: 10.4103/0973-7847.112848
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis pathways of ginkgolides

Abstract: The ginkgolides, acting as anti-platelet-activating factors, have been studied for many years. The biosynthetic pathway of ginkgolides is still far away from unveiling at the level of molecular genetics and biochemistry. There are at least 11 kinds of enzymes having been cloned from Ginkgo biloba L., which catalyze the formation of ginkgolides via a series of reactions. Some researchers have indicated that the addition of precursors and elicitors can influence the accumulation of ginkgolides in the suspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Vascular plants are unique because they retain and use both pathways (Lange et al, 2000;Laule et al, 2003). To date, diterpenoids such as ginkgolides in ginkgo plant are derived from IPP through the MEP pathway (Zeng et al, 2013;Zhao et al, 2013). However, feeding studies by Schwarz (1994) demonstrated that ginkgolides in non-green cultures of G. biloba are derived from the labeled substrates of 13 Cmevalonate.…”
Section: Discussionmentioning
confidence: 95%
“…Vascular plants are unique because they retain and use both pathways (Lange et al, 2000;Laule et al, 2003). To date, diterpenoids such as ginkgolides in ginkgo plant are derived from IPP through the MEP pathway (Zeng et al, 2013;Zhao et al, 2013). However, feeding studies by Schwarz (1994) demonstrated that ginkgolides in non-green cultures of G. biloba are derived from the labeled substrates of 13 Cmevalonate.…”
Section: Discussionmentioning
confidence: 95%
“…Ginkgo biloba has several cardioprotective effects, including improvement of atherosclerosis due to their ability to block platelet-activating factor and platelet aggregation in rats (Zeng et al, 2013;Huang et al, 2014).…”
Section: In Vivo Preclinical Evaluation Of Ginkgo Bilobamentioning
confidence: 99%
“…It has been proposed that Ginkgo biloba extract (GbE) might have positive effects on hyperglycemia. This plant extract mainly contains around 24% flavonoid glycosides and 6% terpenoids, including A, B, C, M, J, P, and Q ginkgolides [ 13 ].…”
Section: Introductionmentioning
confidence: 99%